Dynamic optimization of an Intensive Energetically Integrated Large-Scale Process - Rodriguez, Mariela (2010)
Fil: Rodriguez, Mariela. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química, PLAPIQUI. CONICET. Bahía Blanca, Argentina.